O razdelenii sporta i ozdorovitel'noi fizicheskoi kul'tury - Kim, V. V.; Latipov, M. M.; Linkova, N. A.; Kham, G. S. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
In 1999 the State Duma of Russian Federation authorized the law "About physical culture and sports in Russian Federation". There is a sharp necessity for occurrence of the state law "About professional sports in Russian Federation" now. The occurrence of the law about professional sports will precisely define the borders of the activity of athletes, children, teenagers, and under the legislative contracts will ensure with all social guarantees, which are not present now. Children should be engaged in sports from the obligatory sanction of the is parents on the basis of professional contracts.